The Use of Multitrack Diplomacy in The Liberation Of 10 Indonesian Ship Crew From The Abu Sayyaf Group 2016 - Putu Ratih Kumala Dewi (Department of International Relations, Universitas Andalas, 2019)
Indonesia was again shocked by the events of ship hijacking and hostage-taking of 10 Indonesian ship crew by the Abu Sayyaf separatist group in the Southern Philippines. This is not the first time for Indonesia where its citizens are held hostage by separatists, but the success of the Indonesian government in releasing hostages from Abu Sayyaf's group is interesting to discuss because 10 Indonesian ship crew members who were hostages were able to be released less than 3 months after the hijacking, without ransom and without firing contact. So the question arises as to how Indonesia’s diplomacy strategy is in the release of 10 Indonesian ship crew from the Abu Sayyaf group? In answering the above questions, the writer used the concept of diplomacy, multi-track diplomacy, and peacemaking. The results of this study are the diplomacy strategy used by Indonesia is Total Diplomacy where in addition to running the first track diplomacy also runs second track diplomacy involving track two (non-governmental and professional actors) and track four (civilian population). Keywords: Indonesian Diplomacy, Abu Sayyaf, Multi-Track Diplomacy, Total Diplomacy